Biomarcadores bioquímicos em ostras do gênero CRASSOSTREA para monitoramento ambiental na Baía de São José- Maranhão - NOLETO, Katherine Saldanha (2018)
The aquatic environments of São José Bay (Maranhão) do not have a systematic program of biomonitoring yet. Thus, the objective of this study was to compare biochemical, histological and microbiological biomarkers in oysters for differentiation of regions with varying levels of environmental impactt in São José Bay. Oysters were collected on Curupú Island and Braga’s Harbor between January and October of 2017. Ninety six (96) oysters were collected to quantify the enzymatic activity of biochemical biomarkers Glutathione-S-Transferase (GST) and Catalase (CAT) and histological biomarkers performed on the gills. Water and sediment samples were collected for microbiological analyzes of heavy metals and ammonia. Microbiological analyzes of the water were analyzed by the NMP (most probable number) of total coliforms, E. coli and the total coliform NMP in the oysters, coliform 45 ºC, count of aerobic mesophilic bacteria, Staphylococcus and Salmonella. The results indicated that there was a differentiated pattern in the activity of the GST and CAT enzymes of the analyzed oysters. The results showed that there was a differentiated pattern in the activity of the GST and CAT enzymes of the oysters analyzed, indicating an enzymatic system depleted of the organisms analyzed in the Braga’s Harbor. The histological analysis of the oysters indicated the presence of bacteria of the Rickettsiae type, protozoa of the genus Ancistrocoma, metazoa of the genus Tylocephalum, Haplosporidium and Marteilia Refrigens. The gill changes observed in oysters, especially in the Braga’s Harbor, were lamellae fusion and epithelial hyperplasia, characterizing that there are impacts occurring in the study area. The result of the microbiological analyzes of the water withdrawn from each collection point and the meats of the oysters were within the standards allowed by national legislation. The result data which were obtained in this study suggest that the changes enzymatic of Glutathione-S-Transferase and Catalase in the analyzed oysters are indicative of initial stress caused by the contamination effect that are discharged into the São José Bay, especially in the Braga’s Harbor area. These oysters have the proper microbiological quality, but they contain pathogens that can harm the health of the consumer.